Modelling of incident wave sound absorption coefficient of paper sludge panels - Astrauskas, Tomas; Grubliauskas, Raimondas (International Conference “Environmental Engineering”, 2020)
Paper sludge is the water treatment waste, which produced during paper production. Paper sludge (PS) waste utilization is the common problem in the EU and internationally. According to authors Frías et al. paper sludge is the main waste in the paper processing factories, the percentage reach 35% of product volume. According to the waste management directive No. 2008/98/EC, paper sludge waste should not be utilised in landfills. Such legislation generates the motivation of this study. This study deals with paper sludge as sound absorbing material. In this paper panels made of paper sludge is studied. Sound absorption coefficient of the panels predicted with Horoshenkov and Swift acoustic model for granular media. The aim of this paper is to predict sound absorption coefficient using non-acoustic parameters of the material.